Analysis and management of business value in crisis conditions (Journal of Economic Research & Business Administration, 2018)
The article examines the problem of analyzing the consequences of the financial and economic crisisin terms of impact on the value of business with the purpose of applying restructuring procedures, takinginto account the current legislative framework. The solution to this problem is to solve the scientifictask of adapting existing mathematical and instrumental methods of business valuation in the Republicof Kazakhstan. Restructuring is also considered in the process of cost management in the following situations:under normal, systematic development of the company in a favorable macroeconomic environment,such as cost optimization, working capital management, etc .; in the deterioration of performanceand the company’s condition under the influence of external factors or internal causes. When identifyingnegative factors in the planned development of the company and in crisis situations, various measurescan be taken: under favorable environmental conditions and market growth, the company pays specialattention to optimizing business processes and increasing the cost of business; in worsening macroeconomicfactors or inefficient business processes, technology lagging, promotion of competition and lossof market share is necessary to improve its stability, solvency, improve business processes and systemsfor business recovery. Realization of these goals implies solving the tasks of business management inthe context of overcoming the consequences of the crisis through the application of various companymanagement strategies. As a result, companies can build a flexible business management system that canmeet the challenges in order to reduce the negative effects of the crisis in the short term and to ensuresustainable development and the growth of their value in the long term.